The Impact of Air Pollution on Disease Activity in Bullous Pemphigoid and Pemphigus - Ron Feldman; Emily F. Cole (JID Innovations)
With a growing awareness of climate change, air pollution has emerged as an important contributor to the development and exacerbation of inflammatory skin conditions. However, the effect of air pollution on immunobullous disease activity is unknown. In this study, we performed a retrospective cohort study of 115 patients with bullous pemphigoid and 152 patients with pemphigus from a university-based specialty clinic in the Southeastern United States. We compared standardized disease activity measures with inhalable particulate matter (particulate matter ≤2.5, particulate matter ≤10), ozone, atmospheric pollutants (sulphur dioxide, carbon monoxide, nitrogen dioxide), and air quality index. Results demonstrated small but statistically significant associations between Bullous Pemphigoid Disease Area Index total activity score and several variables (particulate matter ≤2.5, sulphur dioxide, and air quality index). In addition, there were small but significant negative correlations between ozone and bullous pemphigoid disease area index pruritus score as well as carbon monoxide and pemphigus disease area index score. This study suggests that air pollution may impact disease activity in bullous pemphigoid to a greater extent than pemphigus. Future studies should be aimed at identifying potential mechanisms for this association.